Establishing a circular economy framework in the agro-waste to ethanol-based supply chain in Karnataka, India - Mohanty, Reema; Patil, Balachandra; Srinivasaiah, Dasappa (Frontiers in Sustainability, 2024)
Waste handling is one of the biggest problems across the globe. An additional challenge of mitigating the climate change problem also arises during burning of the fossil fuel. The fossil fuel-based transportation system in the country is making air pollution problem worse for the people. To handle these problems, a sustainability assessment framework is introduced in the proposed work. Ethanol, a member of biofuel family is one of the cleanest and most sustainable forms of energy sources. The purpose of this research is to develop a sustainability assessment framework to investigate the environmental feasibility of a supply chain system in terms of end-to-end solution, as well as how it would benefit the transportation sector. A second generation(2G) ethanol- based supply chain is being addressed, and agro-waste such as corn cobs and paddy straw are being considered for the proposed work. The assessment is carried out using a heuristic-based method, known as particle swarm optimization (PSO) technique within the framework of circular economy. The results show that the biomass collection in the proposed area produces on average 2.5 tons of CO2 per hectare area which is much lesser in comparison to 996.6 tons per hectare area of middle east, the main source of fossil fuel. In the future, the planned study would benefit the enterprises and government organizations to establish 2G ethanol plants.